2010
DOI: 10.1080/15287394.2010.484338
|View full text |Cite
|
Sign up to set email alerts
|

Three Structurally Different Polychlorinated Biphenyl Congeners (Pcb 118, 153, and 126) Affect Hormone Production and Gene Expression in the Human H295R In Vitro Model

Abstract: Polychlorinated biphenyls (PCB) are ubiquitous environmental pollutants that have been linked to adverse health effects including endocrine disruption. This study compared the mono-ortho-substituted PCB 118 and di-ortho-substituted PCB 153 with the non-ortho-substituted PCB 126, for possible effects on steroid hormone production and on the expression of 10 genes encoding proteins involved in steroidogenesis. The H295R human adenocarcinoma cell line was used as an in vitro model. Cells were exposed for 48 h to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
4
21
1
Order By: Relevance
“…The induction of CYP19 gene expression may be a possible mechanism for the increase in E2 and the decrease in T production. There were some cases in which the results of hormone production and CYP19 gene expression were consistent with each other [29]. Kraugerud et al found that PFOS caused a numerically higher level of E2 followed by a concentration-response relationship, and E2 was significantly elevated at 600 mM PFOS [30].…”
Section: Discussionmentioning
confidence: 69%
“…The induction of CYP19 gene expression may be a possible mechanism for the increase in E2 and the decrease in T production. There were some cases in which the results of hormone production and CYP19 gene expression were consistent with each other [29]. Kraugerud et al found that PFOS caused a numerically higher level of E2 followed by a concentration-response relationship, and E2 was significantly elevated at 600 mM PFOS [30].…”
Section: Discussionmentioning
confidence: 69%
“…Earlier studies demonstrated disruption of estrus and menstrual cycles in rats and primates [112][113][114][115], and the negative effects of several PCB mixtures on the fertilizability of murine oocytes [116][117][118]. More recently, altered synthesis of estradiol, testosterone, and progesterone by human cell cultures was reported following treatment with individual PCB congeners [119]. The "dioxin-like" PCB congener #77 was also found to decrease fertilization potential in murine oocytes when female mice were fed a contaminated diet [120].…”
Section: Exposure To Polychlorinated Biphenylsmentioning
confidence: 98%
“…In addition, the H295R model was used to evaluate modulation of steroidogenic hormone production by single polychlorinated biphenyl (PCB) congeners [23], emerging pollutants (e.g., perfluorinated compounds) [24], and pharmaceuticals [19,71]. It was also deployed to look at effects of estrogenic mycotoxin, zearalenone, and the metabolites, a-and b-zearalenol.…”
Section: Endocrine Disruption At Hormone-production Levelmentioning
confidence: 99%
“…Recent advances in cell biology and biotechnology have allowed development of a new generation of bioassays focused on hormonal nuclear receptor signaling [14][15][16][17][18] and steroidogenesis pathways [11,[19][20][21][22][23][24][25]. Some of these new bioassays are based on the ability to introduce specific properties and reporter genes into stable cellular systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation